EFEKTIVITAS METODE THE DICTOGLOSS UNTUK KETERAMPILAN MENYIMAK DAN MENULIS BAHASA ARAB SISWA KELAS VIII MTs MUHAMMADIYAH BLIMBING SUKOHARJO: THE EFFECTIVENESS OF THE DICTOGLOSS METHOD FOR ARABIC LISTENING AND WRITING SKILLS FOR CLASS VIII STUDENTS AT MTs MUHAMMADIYAH BLIMBING SUKOHARJO - Istaqim, Rijal; Irawati, Retno Purnama (Universitas Negeri Semarang, 2024)
Arabic listening and writing skills are important aspects of language learning that require innovative learning approaches. Especially at the secondary education level, such as class VIII MTs Muhammadiyah Blimbing Sukoharjo, the mainchallenge in developing these skills is involving students actively in the learning process. Competency in the Arabic listening and writing skills of class VIII students at MTs Muhammadiyah Blimbing Sukoharjo is still felt to be lacking, this isinfluenced by several factors, both in terms of facilities and infrastructure, or learning methods that are not in accordance with listening and writing skills. These two skills require innovative and creative learning methods. Therefore, this research is motivated by the need to find effective learning methods and motivate students to improve their listening and writing skills in Arabic. This research aims to evaluate the effectiveness of The Dictogloss method in improving the Arabic listening and writing skills of class VIII students at MTs Muhammadiyah Blimbing Sukoharjo.This research uses a quantitative approach with test and non-testinstruments. The aim of the research involves analyzing the effectiveness of The Dictogloss method on students' speaking and listening skills and finding out the application of the method.The research results showed that the application of The Dictogloss method significantly improved the listening and writing skills of class VIII students at MTs Muhammadiyah Blimbing Sukoharjo. The experimental class showed an increase in the average pre-test score for listening skills from 68.71 to 72.76 on the post-test, and an increase in the average pre-test score for writing skills from 75.76 to 85.50 on thepost-test. Meanwhile, the control class showed a lower increase, with an average pre-test score for listening skills of 68.06 to 71.88 on the post-test, and an average pre-test score for writing skills of 72.35 to 77. .76 on the post-test. By using the t-test, tcount = -3.243200853, while the t table for N=68 and dk=66 is 1.668270514, with a significance level of 5%. Therefore, this study concludes that the application of The Dictogloss method effectively contributes to improving the Arabic listening and writing skills of class VIII students at MTs Muhammadiyah Blimbing Sukoharjo.